Mechanical plaque control of the interdental space with the "Heidelberg set" - Staehle, Hans Jörg; Frese, Cornelia; Sekundo, Caroline (Quintessence international, 2021)
At present, the most important criterion for the size selection of interdental brushes is the PHD-value (passage hole diameter) according to the ISO standard for interdental brushes ISO 16409:2016. The PHD size range of commercially available products currently lies between 0.6 and 5.2 mm. With the exceptions of special situations, a range between 0.7 and 2.9 mm is sufficient for clinical routine. As most products have longer filaments nowadays, one brush can often be applied for two PHD intervals. Consequently, adequate patient counseling and the individual selection of the appropriate interdental brushes can generally be achieved with an assortment of 12 systematically arranged interdental brush sizes. An application example is the "Heidelberg set" described herein. It is crucial that the correct choice of size is based upon continuously rising PHD-values, and not upon parameters such as stem size, outer diameter of filaments, or similar, as these do not allow for a reliable conclusion regarding the interdental passage.The usage of ISO sizes is also not recommendable due to their insufficient size differentiation.
Gesehen am 23.02.2021